Diagnostic Time Lag of Pediatric Haemophagocytic Lymphohistiocytosis and Patient Characteristics: A Retrospective Cohort Study - Li, Xun; Yan, Haipeng; Xiao, Zhenghui; Zhang, Xinping; Huang, Jiaotian; Xiang, Shi-Ting; Zheng, Mincui; Yao, Zhenya; Zang, Ping; Zhu, Desheng; Li, Liping; Lu, Xiulan (Frontiers in Pediatrics, 2021)
The difficulties and challenges of applying the HLH-2004 diagnostic criteria to early identification and diagnosis of haemophagocytic lymphohistiocytosis have been fully addressed in previous studies. However, the distribution of the diagnostic time lag of haemophagocytic lymphohistiocytosis and related patient characteristics remain unclear. This study investigated the time lags between symptom onset and diagnosis and between hospital admission and diagnosis among pediatric patients with haemophagocytic lymphohistiocytosis, and identified factors that associated with a shorter or longer diagnostic time lag. The cohort of patients with haemophagocytic lymphohistiocytosis was drawn from a tertiary children's hospital and consisted of 122 pediatric patients. The distributions of symptom-to-diagnosis and admission-to-diagnosis time lags were assessed. Clinical characteristics within 48 hours of admission and the fulfilment of HLH-2004 diagnostic criteria were compared among admission-to-diagnosis time lag categories. Logistic regression analyses were conducted to identify factors associated with an admission-to-diagnosis time lag >3 days. The median interval from first symptom onset to HLH diagnosis was 12 days (range 4–71 days) and the median interval from hospital admission to HLH diagnosis was 2 days (range 0–23 days). The following factors were negatively associated with admission-to-diagnosis > 3 days: Epstein–Barr virus infection; admission through pediatric intensive care unit; diagnosis established without NK-cell activity and soluble CD25 tests; the performance of all readily available diagnostic tests for HLH (within 48 hours and 72 hours); concurrent fever, splenomegaly, and cytopenias within 48 hours; hemophagocytosis, hypertriglyceridemia and/or hypofibrinogenemia within 48 hours; and elevated ferritin, total bilirubin, alanine aminotransferase, and prothrombin time within 48 hours. Performance of adequate diagnostic tests for HLH is essential for early diagnosis of HLH. Once suspected, immediate and adequate diagnostic tests for HLH should be arranged for PICU patients. Improvements in diagnostic procedures and monitoring plans are needed to promote early diagnosis of HLH.